Hybridization promotes growth performance by altering rumen microbiota and metabolites in sheep - Zhang, Rui; Zhang, Liwa; An, Xuejiao; Li, Jianye; Niu, Chune; Zhang, Jinxia; Geng, Zhiguang; Xu, Tao; Yang, Bohui; Xu, Zhenfei; Yue, Yaojing (Frontiers in Veterinary Science, 2024)
Hybridization can substantially improve growth performance. This study used metagenomics and metabolome sequencing to examine whether the rumen microbiota and its metabolites contributed to this phenomenon. We selected 48 approximately 3 month-old male ♂Hu × ♀Hu (HH, n = 16), ♂Poll Dorset × ♀Hu (DH, n = 16), and ♂Southdown × ♀Hu (SH, n = 16) lambs having similar body weight. The sheep were fed individually under the same nutritional and management conditions for 95 days. After completion of the trial, seven sheep close to the average weight per group were slaughtered to collect rumen tissue and content samples to measure rumen epithelial parameters, fermentation patterns, microbiota, and metabolite profiles. The final body weight (FBW), average daily gain (ADG), and dry matter intake (DMI) values in the DH and SH groups were significantly higher and the feed-to-gain ratio (F/G) significantly lower than the value in the HH group; additionally, the papilla height in the DH group was higher than that in the HH group. Acetate, propionate, and total volatile fatty acid (VFA) concentrations in the DH group were higher than those in the HH group, whereas NH3-N concentration decreased in the DH and SH groups. Metagenomic analysis revealed that several Prevotella and Fibrobacter species were significantly more abundant in the DH group, contributing to an increased ability to degrade dietary cellulose and enrich their functions in enzymes involved in carbohydrate breakdown. Bacteroidaceae bacterium was higher in the SH group, indicating a greater ability to digest dietary fiber. Metabolomic analysis revealed that the concentrations of rumen metabolites (mainly lysophosphatidylethanolamines [LPEs]) were higher in the DH group, and microbiome-related metabolite analysis indicated that Treponema bryantii and Fibrobacter succinogenes were positively correlated with the LPEs. Moreover, we found methionine sulfoxide and N-methyl-4-aminobutyric acid were characteristic metabolites in the DH and SH groups, respectively, and are related to oxidative stress, indicating that the environmental adaptability of crossbred sheep needs to be further improved. These findings substantially deepen the general understanding of how hybridization promotes growth performance from the perspective of rumen microbiota, this is vital for the cultivation of new species and the formulation of precision nutrition strategies for sheep.